Like a Boss - Arteta, Miguel; Byrne, Rose; Hayek, Salma, 1966-; Haddish, Tiffany, 1979-; Coolidge, Jennifer; Porter, Billy; Graynor, Ari; St. Clair, Jessica; Yang, Jimmy O.; Parker, Catherine, 1986-; Soni, Karan, 1989-; Paramount Home Entertainment (Firm) ([Hollywood, CA] : Paramount, 2020)
Best friends Mia and Mel are living their best lives running their own cosmetics company they've built from the ground up. Unfortunately, they're in over their heads financially, and the prospect of a big buyout offer from a notorious titan of the cosmetics industry Claire Luna proves too tempting to pass up, putting Mel and Mia's lifelong friendship in jeopardy. The beauty business is about to get ugly.
Originally released as a motion picture in 2019.
Director, Miguel Arteta.
Rose Byrne, Salma Hayek, Tiffany Haddish, Jennifer Coolidge, Billy Porter, Ari Graynor, Jessica St. Clair, Jimmy O. Yang, Catherine Parker, Karan Soni.
MPAA rating: R.
DVD.
English audio.
Keywords: Cosmetics industry -- Drama; Businesswomen -- Drama; Debt -- Drama; DVD-Video discs; Feature films; Comedy films